1987
DOI: 10.1021/j100310a005
|View full text |Cite
|
Sign up to set email alerts
|

Electron-transfer times are not equal to longitudinal relaxation times in polar aprotic solvents

Abstract: It has been found that the electron-transfer time ret of the intramolecular electron-transfer reaction of electronically excited bianthryl is not equal to the longitudinal relaxation time of the solvent in various polar aprotic solvents. This demonstrates that the recently observed agreement of ret and r¡, in specific cases, is not general. In addition, microscopic solvation times ts have been measured for the solvents, and it has been observed that t, is very similar to for a broad range of polar aprotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
99
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(108 citation statements)
references
References 0 publications
8
99
0
Order By: Relevance
“…Thus the shorter time scale measurements are consistent with our previous results which showed that r~ decreases as the temperature increases. For the solvents used in the current experiments, only in the case of ethylacetate our results can be compared with the ultrafast dynamics studies reported elsewhere [22,23]. The solvation times for ethylacetate obtained elsewhere [22,24] are 2.3 ps (coumarin 311) and 2.6 ps (coumarin 102), respectively.…”
Section: C(t) Is Considered To Discuss the Stokes Shift Dynamics Howmentioning
confidence: 55%
See 2 more Smart Citations
“…Thus the shorter time scale measurements are consistent with our previous results which showed that r~ decreases as the temperature increases. For the solvents used in the current experiments, only in the case of ethylacetate our results can be compared with the ultrafast dynamics studies reported elsewhere [22,23]. The solvation times for ethylacetate obtained elsewhere [22,24] are 2.3 ps (coumarin 311) and 2.6 ps (coumarin 102), respectively.…”
Section: C(t) Is Considered To Discuss the Stokes Shift Dynamics Howmentioning
confidence: 55%
“…For the solvents used in the current experiments, only in the case of ethylacetate our results can be compared with the ultrafast dynamics studies reported elsewhere [22,23]. The solvation times for ethylacetate obtained elsewhere [22,24] are 2.3 ps (coumarin 311) and 2.6 ps (coumarin 102), respectively. Comparing these values with the results of Table 2 it is seen that the magnitude of r~ for fluoroprobe in ethylacetate is in good agreement with the results of Barbara's group.…”
Section: C(t) Is Considered To Discuss the Stokes Shift Dynamics Howmentioning
confidence: 55%
See 1 more Smart Citation
“…Solvent is coupled by changes in local electric fields that accompany electron transfer (Ulstrup 1979;Dogonadze et al 1985;Reichardt 1988;Chen & Meyer 1998). Dynamics of solvent coupling have been measured by observing absorption band shifts following ultrafast laser excitation of charge transfer transitions (Kahlow et al 1987;Horng et al 1995;Fleming & Cho 1996).…”
Section: It Icmentioning
confidence: 99%
“…[32][33][34][35] Most of the experimental data on solvation dynamics in polar solvents have been obtained using a time-resolved fluorescence method with upconversion. [36][37][38][39][40][41][42][43][44][45][46] The energy difference in the ground and excited electronic states of the solute is manifested through (t), the frequency of the fluorescence spectral maximum of the molecule. Its timeevolution ͑dynamic Stokes shift, DSS͒ reflects the solvation dynamics of the electronically excited solute.…”
Section: Introductionmentioning
confidence: 99%